2021
DOI: 10.1093/toxsci/kfab010
|View full text |Cite
|
Sign up to set email alerts
|

In UteroMaternal Benzene Exposure Predisposes to the Metabolic Imbalance in the Offspring

Abstract: Environmental chemicals play a significant role in the development of metabolic disorders, especially when exposure occurs early in life. We have recently demonstrated that benzene exposure, at concentrations relevant to cigarette smoke, induces a severe metabolic imbalance in a sex-specific manner affecting male but not female mice. However, the roles of benzene in the development of aberrant metabolic outcomes following gestational exposure, remain largely unexplored. In this study, we exposed pregnant C57BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…However, only male offspring of DEP-exposed dams exhibited exaggerated weight gain, insulin resistance, and anxiety-like behavior when challenged with HFD compared with male control offspring ( 69 ). In support, we have previously demonstrated that maternal exposure to inhaled benzene throughout pregnancy was associated with hyperglycemia, insulin resistance, reduced energy expenditure, and increased hepatic inflammation in the adult male offspring ( 73 ). Similarly, exposure to benzene in adulthood was also associated with a metabolic imbalance in male but not female mice ( 74 ).…”
Section: Hypothalamic Response To Pollutants: Neuroinflammation and A...supporting
confidence: 70%
See 2 more Smart Citations
“…However, only male offspring of DEP-exposed dams exhibited exaggerated weight gain, insulin resistance, and anxiety-like behavior when challenged with HFD compared with male control offspring ( 69 ). In support, we have previously demonstrated that maternal exposure to inhaled benzene throughout pregnancy was associated with hyperglycemia, insulin resistance, reduced energy expenditure, and increased hepatic inflammation in the adult male offspring ( 73 ). Similarly, exposure to benzene in adulthood was also associated with a metabolic imbalance in male but not female mice ( 74 ).…”
Section: Hypothalamic Response To Pollutants: Neuroinflammation and A...supporting
confidence: 70%
“…In support, we have previously demonstrated that maternal exposure to inhaled benzene throughout pregnancy was associated with hyperglycemia, insulin resistance, reduced energy expenditure, and increased hepatic inflammation in the adult male offspring (73). Similarly, exposure to benzene in adulthood was also associated with a metabolic imbalance in male but not female mice (74).…”
Section: Hypothalamic Response To Pollutants: Neuroinflammation and A...supporting
confidence: 69%
See 1 more Smart Citation
“…With regard to prenatal exposure, Koshko et al, demonstrated that benzene induce metabolic perturbation (energy homeostasis and glucose metabolism), more severe in male offspring than in females [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prenatal exposure in in vivo experiments demonstrated that benzene could cross the placenta and reach the fetus, and different sex-based effects were observed [ 53 ]. In agreement with the greater susceptibility of males to benzene effects, male fetuses appeared more vulnerable to oxidative stress caused by benzene exposure [ 56 ] while adult male offspring developed insulin resistance [ 53 ]. In addition, offspring showed a trend of higher development of hepatic tumors in males and hematopoietic tumors in females.…”
Section: Discussionmentioning
confidence: 99%